Heavy Metal Adsorption Using Cellulose Xanthate from Sugarcane Bagasse: A Fixed-Bed Column Study - Iryani, Dewi Agustina; Permadi, Sigit; Astuti, Widi; Sumardi, Slamet; Taharuddin, Taharuddin (Jurnal Rekayasa Kimia & Lingkungan, 2025)
In recent years, various environmentally friendly adsorbents have been developed to address the removal of heavy metals from industrial wastewater. This study focuses on the adsorption of lead (Pb) and copper (Cu) using cellulose xanthate derived from sugarcane bagasse as an adsorbent. The adsorption experiments were conducted in a fixed-bed column with dimensions of 2.4 cm in diameter and 8 cm in height. Atomic Absorption Spectrophotometry (AAS) was used to analyze the concentrations of Pb and Cu before and after adsorption, while the adsorbent composition was characterized using X-Ray Fluorescence (XRF). The breakthrough times for Pb and Cu adsorption was found to be 8 and 6 minutes, respectively, with total adsorption durations of 18.584 and 17.543 minutes. The Thomas Model was employed to evaluate the kinetics and adsorption capacity, yielding kinetic constants (KTH) of 0.00283 and 0.0006 mL/mg.min for Pb and Cu, respectively, and adsorption capacities (qeq) of 712.89 and 181.18 mg/g. These results provide valuable insights into the adsorbents efficiency, kinetics, and potential applications in environmental remediation and wastewater treatment.